ANALISIS METODE ALTMAN Z-SCORE DAN METODE ZMIJEWSKI UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PT FAST FOOD INDONESIA TBK PERIODE 2013-2022 - Erika Aditha Iyoy; Ferdina Watiningsih (Journal of Research and Publication Innovation, 2024)
This research aims to determine the level of bankruptcy of PT Fast Food Indonesia, Tbk based on analysis of the Altman Z-score method and the Zmijewski method. The research method used is quantitative descriptive method and secondary data collection. The population of this research is the financial report of PT Fast Food Indonesia, Tbk and the sample used in this research is the balance sheet and profit and loss report for 10 years from 2013-2022. The results of the analysis of the Altman Z-score calculation, on average, were in the healthy zone or safe zone in the 2013-2019 period and in the 2020-2022 period the company was in the grey zone or prone to bankruptcy. Analysis of Zmijewski's calculations shows that on average the company was in the healthy zone in the 2013-2020 and 2022 periods, only 1 period for the company, namely in 2021, the company was in the zone of potential bankruptcy.